Sosialisasi Tentang Partisipasi Wanita Dalam Dunia Olahraga - Munandar, Wahyu (Yayasan Habiburrahman Jamalu Bina Ummat, 2024)
Women often do not have the space to participate in the world of sports because of society's view that sports activities require a strong physique so participants are dominated by men. This activity is a community service carried out at the TNI AL Makassar Health Vocational School which aims to provide education that free space is open for women to be involved in sports activities. Even though there are many challenges faced by women if they want to excel, this activity provides several tips and tricks on how to start and maintain women's consistency in sports and provides examples of sports that are suitable for women. This activity was carried out in one of the halls which was attended by students of the Makassar TNI AL Health Vocational School on Thursday, June 27 2024.